Solidification behavior and environmental risk assessment of toxic elements on tailings from carbothermic reduction-magnetic separation of lead blast furnace slag - jiang, ziwei (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Lead blast furnace slag (LBFS) generated during lead smelting is a hazardous solid waste containing potentially toxic elements (Pb, Zn, As, and Cd) with high mobility and solubility. In this study, a process for the utilization of LBFS by carbothermic reduction-magnetic separation method is proposed. Leaching toxicity and Tessier sequential extraction experiments were conducted on LBFS and magnetic separation tailings (TS), and the environmental risk was evaluated using the risk assessment coding index and potential ecological risk index. The obtained results showed that the potentially toxic elements in the TS were solidified in the spinel phase or silicate phase. In addition, the XRD, SEM-EDS, and FTIR results showed the formation of PbCa2Si3O9, ZnAl2O4, and Ca3(AsO4)2 phases. The leaching concentrations of Pb, Zn, As, and Cd in TS were much lower than the toxicity characteristic leaching procedure (TCLP) and China standard leaching test (CSLT) limits. The results of Tessier sequential extraction procedure confirmed that the proportions of the stable residual state of the potentially toxic elements in TS were significantly higher than in LBFS. Furthermore, the ecological environmental risk level for the TS decreased significantly compared to that of LBFS.